Accessible dynamic micropatterns in monolayer cultures via modified desktop xurography. (10th March 2021) - Tran, Raymond; Hoesli, Corinne A; Moraes, Christopher
Abstract: Micropatterned cell cultures provide an important tool to understand dynamic biological processes, but often require specialized equipment and expertise. Here we present subtractive bioscribing (SuBscribing), a readily accessible and inexpensive technique to generate dynamic micropatterns in biomaterial monolayers on-the-fly. We first describe our modifications to a commercially available desktop xurographer and demonstrate the utility and limits of this system in creating micropatterned cultures by mechanically scribing patterns into a brittle, non-adhesive biomaterial layer. Patterns are sufficiently small to influence cell morphology and orientation and can be extended to pattern large areas with complex reproducible shapes. We also demonstrate the use of this system as a dynamic patterning tool for cocultures. Finally, we use this technique to explore and improve upon the well-established epithelial scratch assay, and demonstrate that robotic control of the scratching tool can be used to create custom-shaped wounds in epithelial monolayers, and that the scribing direction leaves trace remnants of matrix molecules that may significantly affect conventional implementations of this common assay.